1997
DOI: 10.1590/s0036-46651997000400005
|View full text |Cite
|
Sign up to set email alerts
|

Peptic disease and Helicobacter pylori are highly prevalent in patients with the indeterminate form of chagas’ disease: report of 21 cases

Abstract: Given that chagasic patients in the indeterminate form of this disease, can have abnormal motility of the digestive tract and immunologic abnormalities, we decided to assess the frequency of peptic disease and Helicobacter pylori (Hp) infection in these individuals. Twenty-one individuals, 13 males and 8 females, mean age 37.6 +/- 11.1 years, were examined. Biopsies of the duodenum, antrum, lesser and greater gastric curvature and esophagus were performed. The endoscopic findings were of chronic gastritis in 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
8
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 12 publications
3
8
0
Order By: Relevance
“…The high prevalence of co-infection with T. cruzi and H. pylori in our study (approximately 70%) and in other studies is not surprising because the transmission of both of these pathogens is associated with poor socioeconomic conditions [13][14][15][16][17] . Moreover, in Brazil, which is considered a developing country, the overall prevalence of H. pylori is high and varies from 55% to 87% according to the geographical region 30,31 .…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…The high prevalence of co-infection with T. cruzi and H. pylori in our study (approximately 70%) and in other studies is not surprising because the transmission of both of these pathogens is associated with poor socioeconomic conditions [13][14][15][16][17] . Moreover, in Brazil, which is considered a developing country, the overall prevalence of H. pylori is high and varies from 55% to 87% according to the geographical region 30,31 .…”
Section: Discussionsupporting
confidence: 67%
“…We found a high prevalence of gastritis and H. pylori infection in both groups of chagasic and non-chagasic patients in the present study. Although two previous studies have reported similar fi ndings for a small group of chagasic patients 13,14 , this is the fi rst controlled study to demonstrate that H. pylori is the major cause of gastritis in patients with Chagas disease.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Later, some studies demonstrated a high prevalence of H. pylori infection in patients with Chagas disease [13][14][15][16] . As this small number of studies on T. cruzi and H. pylori co-infection had no control groups and/or included a low number of patients, we evaluated the prevalence of H. pylori infection among chagasic and non-chagasic subjects living in a region previously considered endemic for Chagas disease.…”
Section: Introductionmentioning
confidence: 99%